Perancangan Model Bisnis Menggunakan Business Model Canvas (Studi pada UMKM Boss Talasik) - Salman Ramadan Nur Alam; Sunu Puguh Hayu Triono (IPM2KPE, 2023)
This research aims to find out the business models currently implemented by MSMEs and create suggestions for appropriate business model innovations for Boss Talasik MSMEs. The research method uses qualitative methods with descriptive research types. The results of this research show that there is an innovative business model that can play an important role for MSMEs along with opportunities and threats based on the results of mapping the nine blocks which are equipped with external analysis using the Value Proposition Canvas which describes the benefits according to expectations from customer wants and needs. In conclusion, the business model development of Boss Talasik MSMEs uses the Business Model Canvas approach which is equipped with Value Proposition Canvas analysis and Business Environment Analysis which can provide a new business model proposal for Boss Talasik MSMEs to support excellence in industrial competition. Keywords: Business Model Canvas, Business Model, Value Proposition Canvas